The affect of Musa balbisiana Co//a flesh and seed on rat gastric acid secretion in vitro. - Eti Nurwening Sholikhah Eti Nurwening Sholikhah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Background: The alcoholic extract of kluthuk banana (Musa balbisiana Colla), a seeded banana, has been known to reduce gastric acid secretion on rats, but there is no explanation which part of kluthuk banana having that effect.Objective: To determine the effect of kluthuk banana both flesh and seed on rats gastric acid secretion in vitro.Methods: This study was conducted using isolated Wistar rat stomach. Fifty-four rats of 175-225 g weight were devided into 9 groups, each consisted of 3 male and 3 female rats. The stomach was suspended in an organ bath containing buffered serosal solution, and the gastric lumen was perfused continuously with unbuffered mucosal solution. The isolated preparation was stabilized for 5 times within 1 h and perfusate was spilled out. The perfusate was allowed to flow continuously, collected for 10 minutes duration and Fl+ concentration was measured, as basal FI4- concentration. Pretreatment was added to the unbuffered mucosal solution for 30 minutes, after which, histamine was added to the unbuffered mucosal solution for 80 minutes to induce gastric secretion. Perfusate from gastric lumen were collected every 10 minutes and FP-concentration was measured. The elevation of H* concentration was calculated in percentage, and was expressed as means Â± SEM. ANOVA was used to analysis the data.Results: The elevation of H* concentration of groups treated with alcoholic extract of kluthuk banana seed at 12.46, 24.92 and 49.84 mg/kgBW was significantly lower than control group (p0.05).Conclusion: Alcoholic extract of kluthuk banana seed reduced rat gastric acid secretion in vitro, but did not those of alcoholic extract of kluthuk banana flesh.Keywords: Musa balbisiana Colla - gastric acid secretion - histamine - rat - stomach